Exploring Individual Preferences on Protecting Environment: A Binominal Logistic Regression - Esra Karapınar Kocağ (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Validity of Environmental Kuznets Curve (EKC) hypothesis has been tested by several researchers. While macro approaches towards EKC hypothesis are largely discussed in the literature, microeconomic approaches are quite scarce. This paper, in this respect, aims to provide individual insights on the environmental preferences. Using individual priority towards environmental protection rather than economic growth as an environmental indicator, I investigate individual factors affecting this preference. To the best of my knowledge, this study is the first attempt that explains individual environmental preferences by a wide range of individual characteristics exploiting individual observations from more than a hundred countries for the period of 1995-2020. The findings indicate that there is no clear evidence to support EKC hypothesis. However, significant effects of age, gender, education, unemployment, along with further significant explanatory variables are expected to be useful to make appropriate policies for a greener future.